Media, memory, and the First World War - Williams, David, 1945- (McGill-Queen's studies in the history of ideas ;, 2009)
Of interest to historians, classicists, media and digital theorists, literary scholars, museologists, and archivists, Media, Memory, and the First World War is a comparative study that shows how the dominant mode of communication in a popular culture - from oral traditions to digital media - shapes the structure of memory within that culture.